Effects of configuration on the operation of membranes in membrane biological reactors - Winkler, Gudrun (Cranfield University, 2011)
The aim of this work included the investigation of the impact of membrane material properties on fouling propensity and permeate flux decline in MBR biomass systems. Furthermore, the impact of membrane configuration on the respective fouling behaviour was of interest. A direct comparative study of different membrane module configurations including a multi-tubular membrane (MT), a single flat sheet module (FS) and a hollow fibre (HF) pilot scale module was undertaken. Membrane module filtration performances, especially with respect to their fouling propensity under varying hydraulic conditions, were investigated to ultimately evaluate the impact of varying parameters such as aeration and biomass make up on fouling and to determine optimised operational parameters. Subsequently, a range of different membrane materials, such as flat sheet membrane samples made of polyethylene (PE), polyethersulfone (PES), polysulfone (PS) and polyvynilidene fluoride (PVDF) and a single-tube made of PVDF and PES were characterised and their fouling propensity to MBR biomass was studied at bench-scale. Cont/d.